ANALISIS KINERJA RANTAI PASOK CABAI RAWIT DI KECAMATAN DUKUN KABUPATEN MAGELANG - Muhammad Rafli Arfiyan; Dwi Aulia Puspitaningrum; Heni Handri Utami (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
The study is a quantitative descriptive study with purpose of evaluating the effectiveness of the cayenne pepper supply chain. In this method, non-probability sampling is used. Analyze the information using the Supply Chain Operation Reference (SCOR). The cayenne pepper supply chain's performance was evaluated using five different approaches; chain I and chain II produced the greatest results in terms of cayenne pepper delivery efficiency. According to criteria, the outcome is 97,20 percent on chain I and 98 percent on chain II, including superior. When compared to Chain I, Chain II must have an order fulfillment rate of 7,9 percent, placing it in the below parity category. If supply chain I is flexible for three days while supply chain II is flexible for one and a half days, it is highly profitable. Chain I in the superior category has a lead time of three days, whereas chain II has a lead time of just one day. While the Chain II cycle has a superior category of 1,6 days, the Chain I order fulfillment period is 3,3 days. Chain II for 0,53 days and Chain I for 0,0079 days are regarded as superior daily supplies. Chain-to-cash cash cycles of 1,079 days and chain II cycles of 2,53 days were among the better categories. The results of the study demonstrate that although the cayenne pepper supply chain performs admirably overall, order fulfillment is still fairly low.